Method for testing content of titanium and calcium in titanium-containing PET (Polyethylene Terephthalate) plastic
By using the digestion methods of sulfuric acid carbonization, nitric acid and hydrofluoric acid in PET plastic detection, the problem of incomplete digestion in the prior art has been solved, and high accuracy and high precision detection of titanium and calcium content is achieved, ensuring the accurate evaluation of PET quality.
Patent Information
- Application Number
- CN202411970714.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
When the prior art detects the titanium and calcium content in titanium-containing PET plastics, incomplete digestion leads to low accuracy and poor precision in detection results, which affects the accurate judgment of product quality.
The PET plastic samples were digested successively by carbonization of sulfuric acid, nitric acid and hydrofluoric acid. The titanium and calcium content in the digestion solution were detected by ICP-OES to ensure that the sample was completely digested and the insoluble impurities were removed.
It improves the accuracy and precision of the test results, ensures accurate detection of titanium and calcium content, and effectively assists in evaluating PET quality.
Smart Images

Figure BDA0005219442200000061 
Figure HDA0005219442220000011 
Figure HDA0005219442220000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical testing and PET plastic quality testing, and in particular to a method for testing the titanium and calcium contents in titanium-containing PET plastic. Background Art
[0002] Titanium dioxide is a commonly used whitening agent in PET production. Titanium dioxide is a highly efficient white pigment with excellent hiding power and reflective properties, which can effectively improve the whiteness and brightness of PET materials. It is widely used in PET bottles, fibers and other plastic products, especially in products that require high transparency or white appearance. Therefore, titanium content is usually one of the important indicators for PET quality inspection. By testing the titanium content, it can be ensured that the amount of whitening agent added meets the process requirements and avoids excessive or insufficient conditions, thereby ensuring the visual effect and market competitiveness of the product. The detection of calcium content helps to detect whether there are foreign contaminants in PET, especially for recycled PET or products containing other additives. Calcium-based contaminants may have an adverse effect on the processing performance of PET and the quality of the final product, so testing the calcium content helps to ensure the purity and stability of the product.
[0003] Because PET (Polyethylene terephthalate, also known as polyester resin, polyethylene terephthalate or thermoplastic polyester) is not only stable against chemicals, but also resistant to weak acids and organic solvents, the conventional test method currently used is: using a mixed acid of nitric acid, hydrochloric acid and hydrofluoric acid as a digestion solution, treating the sample with microwave digestion-assisted digestion solution and fixing the volume, and then using atomic absorption spectroscopy (AAS), inductively coupled plasma mass spectrometry (ICP-MS) and other methods to detect the content of titanium and calcium in the sample. However, the prior art still has the following technical problems: the prior art using nitric acid, hydrochloric acid and hydrofluoric acid in combination cannot completely digest the sample, and there is white powder or crystals at the bottom of the solution, resulting in insufficient dissolution of the elements in the sample, resulting in low accuracy of the test results; poor precision and poor repeatability, affecting the accurate judgment of product quality.
[0004] In view of this, developing a test method for the titanium and calcium content in titanium-containing PET plastics with good digestion effect and high accuracy can not only effectively make up for the shortcomings of the existing technology, but also accurately detect the content of titanium and calcium in titanium-containing PET, effectively assist in the evaluation of PET quality, and is of great significance to the quality monitoring of PET products. Summary of the invention
[0005] The present invention aims to provide a method for testing the titanium and calcium contents in titanium-containing PET plastics, so as to solve the technical problem in the prior art that inaccurate test results are caused by incomplete digestion of PET.
[0006] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a method for testing the content of titanium and calcium in titanium-containing PET plastic, when detecting titanium: comprising: (i) a digestion stage: the sample is sequentially carbonized with sulfuric acid, nitric acid and hydrofluoric acid to digest the raw material, and the volume is constant to obtain a digestion solution; (ii) a detection stage: ICP-OES detects the digestion solution to obtain the titanium content;
[0007] When detecting calcium: it includes: (i) digestion stage: the sample is successively carbonized with sulfuric acid, digested with nitric acid or hydrochloric acid to obtain a digestion solution; (ii) detection stage: ICP-OES detects the digestion solution to obtain the calcium content.
[0008] The principles and advantages of this solution are:
[0009] Titanium dioxide (TiO2) has stable chemical properties and is insoluble in most acids, but soluble in HF. In this scheme, after PET is completely carbonized by sulfuric acid, the black substance after carbonization is oxidized by nitric acid, and the solution becomes clear, and calcium is also completely dissolved in the solution. At this time, the calcium content in the digestion solution can be detected by constant volume. However, because nitric acid cannot react with titanium compounds, the white powder remaining in the solution at this time is the titanium compound. Then, hydrofluoric acid is added to treat, and the white powder can be completely digested, so that titanium is completely dissolved in the digestion solution. After the digestion solution is filtered to remove insoluble impurities, it is detected by ICP-OES (i.e., inductively coupled plasma emission spectrometer) to obtain the titanium and calcium content in titanium-containing PET. Compared with the existing technology combination that cannot completely acidify the titanium in the sample using sulfuric acid, hydrochloric acid and hydrofluoric acid, this solution can effectively digest the titanium in PET plastic by carbonizing the raw material with sulfuric acid and then digesting it in sequence with nitric acid and hydrofluoric acid, thereby improving the accuracy of titanium content detection in the digestion solution and avoiding underestimation of the titanium content in PET plastic due to low test results caused by incomplete digestion, thereby affecting the application performance of PET plastic.
[0010] In addition, compared with the prior art, in which the digestion process is interrupted and the digestion efficiency is reduced because the digestion solution may need to be removed and cooled before adding the subsequent digestion solution during the heating process of the prior art, the sample in this solution does not need to be cooled during the heat-removal digestion process. The next digestion reagent can be directly added after the staged digestion is completed. Not only will the digestion solution not be splashed due to frequent taking operations, thereby effectively improving the detection accuracy; it also effectively speeds up the digestion speed and improves the sample digestion efficiency. The applicant found through long-term experiments that when detecting Ti, the sample digestion stage of this solution only takes 30 to 40 minutes to complete the digestion, effectively improving the sample digestion efficiency.
[0011] Preferably, as an improvement, in the (i) digestion stage, the volume usage of the sulfuric acid, nitric acid and hydrofluoric acid is 10 to 25 times, 15 to 25 times and 10 to 20 times the mass of the sample, respectively.
[0012] Technical effect: This scheme adopts the above-mentioned setting, which is convenient for fully digesting the substances in the sample raw materials and improving the detection accuracy. The applicant found through long-term experiments that if the amount of sulfuric acid is too little, the residual raw materials will not be carbonized, resulting in incomplete digestion of the substances in the sample, thereby reducing the detection accuracy; if the amount of sulfuric acid is too high, it is not only easy to waste, but also requires excessive addition in the subsequent nitric acid and hydrofluoric acid digestion process, further increasing the amount of reagents, causing waste; on the other hand, too much detection reagent makes it inevitable to splash during the stirring and heating process, causing the loss of the object to be detected (such as titanium), further reducing the detection accuracy. In addition, if too much sulfuric acid is added, the viscosity of the digestion solution will increase, which will have serious physical interference with the ICP-OES test, and then have a greater adverse effect on the ICP-OES test. If the amount of nitric acid is too little, it will not be able to fully destroy the PET structure and dissolve the metal organic matter, so that the detection value is low. If the amount of nitric acid is too much, it will also cause waste, and the digestion solution is too much and easy to swing out of the container, thereby affecting the accuracy of the test results. If there is too little hydrofluoric acid, the titanium-containing compounds cannot be fully digested, resulting in a low test value.
[0013] Preferably, as an improvement, in the (i) digestion stage, polytetrafluoroethylene beakers are used as containers for the sulfuric acid carbonization raw material, nitric acid and hydrofluoric acid digestion, and heating is performed by a hot plate method.
[0014] Technical effect: This scheme adopts the above-mentioned setting, which is convenient for fully digesting samples while achieving non-toxic detection and reducing safety hazards of detection. The applicant has found through long-term experiments that if a ceramic crucible is used in combination with the dry ashing method to digest the raw materials, it can effectively improve the detection value compared with the microwave digestion method. However, because the ceramic crucible contains a large amount of calcium and other elements, on the one hand, it seriously pollutes the calcium test; on the other hand, the ceramic crucible and hydrofluoric acid contact reaction generate silicon tetrafluoride (SiF4) or other by-products, resulting in serious pollution and inconvenient for promotion and use.
[0015] Preferably, as an improvement, in the (i) digestion stage, the endpoint of the sulfuric acid carbonization is to completely carbonize the sample into a black liquid, but not boil it dry.
[0016] Technical effect: This scheme adopts the above-mentioned setting, which is convenient for sulfuric acid to fully carbonize and digest the sample. The applicant has found through long-term experiments that if the degree of sulfuric acid carbonization is too shallow, some raw materials will remain due to insufficient carbonization, and the subsequent addition of nitric acid and hydrofluoric acid will have limited destructive effect on the complete PET plastic structure, thereby affecting the accuracy of the test results. If the degree of sulfuric acid carbonization is too deep (such as too much sulfuric acid is added), it will cause the viscosity of the digestion solution to increase, which will have serious physical interference with the ICP-OES test, and thus have a greater adverse effect on the ICP-OES test.
[0017] Preferably, as an improvement, in the (i) digestion stage, the endpoint of the nitric acid digestion is solution clarification.
[0018] Technical effect: This scheme adopts the above-mentioned setting to facilitate the full dissolution of the reaction carbide. The applicant has found through long-term experiments that after nitric acid digests the carbide, the digestion solution becomes clear, and some white powder (such as titanium dioxide, calcium fluoride and certain special additives or pollutants (such as ceramic fiber, metal powder, polymer blends, etc.)) and / or black powder (such as incompletely dissolved carbonized residue) will remain and cannot be completely digested. At this time, subsequent digestion solution can be added to continue digestion, that is, hydrofluoric acid is added to digest silicon compounds.
[0019] Preferably, as an improvement, in the (i) digestion stage, after the hydrofluoric acid digestion, the digestion solution is filtered using a syringe filter.
[0020] Technical effect: This scheme adopts the above-mentioned setting, which is convenient for removing insoluble impurities that cannot be digested by any digestion solution, so as to avoid interfering with the detection process in the subsequent on-machine detection stage and reducing the accuracy of the detection results.
[0021] Preferably, as an improvement, in the (i) digestion stage, the volume of the digestion solution after constant volume is 100 to 150 times the mass of the sample.
[0022] Technical effect: This scheme adopts the above-mentioned setting, which is convenient for fully dissolving the fixed-volume digestion solution, preserving the sample to be tested as much as possible without loss, and improving the accuracy of the test results.
[0023] Preferably, as an improvement, in the (ii) detection stage, the digestion solution is diluted 50 to 100 times before detection.
[0024] Technical effect: This solution adopts the above settings to further reduce detection errors and improve the accuracy of detection results. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a state diagram of the digestion solution obtained by the existing microwave digestion method (the bottom of the test tube in the figure contains a lot of white undissolved matter).
[0026] Figure 2 This is a state diagram of the digestion solution obtained by the existing dry ashing method (showing that the sample is basically digested).
[0027] Figure 3 1 is a state change diagram of the digestion solution in Example 1 of the present invention (the left is a black digestion solution obtained by carbonization with sulfuric acid, and the right is a clear digestion solution obtained by digestion with nitric acid).
[0028] Figure 4 This is a state diagram of the digestion solution obtained by repeating the experiment three times in Example 1 of the present invention (there is basically no undissolved matter at the bottom of the test tube in the figure). DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. Unless otherwise specified, the technical means used in the following examples and experimental examples are conventional means well known to those skilled in the art, and the materials, reagents, etc. used can be obtained from commercial sources.
[0030] Program Overview
[0031] This scheme provides a method for testing the titanium and calcium content in titanium-containing PET plastics, comprising the following steps:
[0032] (i) Digestion stage: When testing titanium, the sample is sequentially carbonized with sulfuric acid, digested with nitric acid and hydrofluoric acid to obtain a digestion solution; when testing calcium, the sample is sequentially carbonized with sulfuric acid, digested with nitric acid or hydrochloric acid to obtain a digestion solution;
[0033] As a reference, the volume dosage of sulfuric acid, nitric acid and hydrofluoric acid is 10 to 25 times, 15 to 25 times and 10 to 20 times the mass of the sample, respectively. Specifically, when the amount of PET plastic sample in this scheme is 0.2 g to 0.5 g, the amount of 98% sulfuric acid is 2 to 5 ml, the amount of 65 to 68% nitric acid is 3 to 5 ml, and the amount of 40% hydrofluoric acid is 2 to 5 ml.
[0034] As a reference, polytetrafluoroethylene beakers (washed and dried after boiling aqua regia) were used as containers for sulfuric acid carbonization, nitric acid and hydrofluoric acid digestion, and heated by electric hot plate method. The end point of sulfuric acid carbonization is to completely carbonize the sample into a black liquid, but it cannot be boiled dry; the end point of nitric acid digestion is to clarify the solution, and some insoluble substances may remain in the solution; after hydrofluoric acid digestion, the digestion solution is filtered using a syringe filter to remove special additives that cannot be digested by the composite digestion solution.
[0035] As a reference, the volume of the digestion solution after constant volume is 100 to 150 times the mass of the sample. Specifically, when the amount of PET plastic sample in this scheme is 0.2 to 0.5 g, the digestion solution after constant volume is 25 to 75 ml, which is convenient for operation. In this embodiment, the PET plastic raw material is specifically 0.2 g, and the digestion solution after constant volume is 25 ml.
[0036] (II) Detection stage: After the digestion solution is diluted 50 to 100 times, the digestion solution is detected by ICP-OES to calculate the titanium and calcium contents. The ICP-OES method for detecting the element content in the solution is an existing technology and will not be described in detail here.
[0037] Comparative method 1: microwave digestion
[0038] Place the sample in a polytetrafluoroethylene beaker and digest it with sulfuric acid, nitric acid / hydrochloric acid and hydrofluoric acid (selected according to the type of metal to be detected) in turn by microwave heating, then adjust the volume and test. For details of the digestion results, see Figure 1 .
[0039] Comparative method 2: dry ashing method
[0040] The sample is placed in a ceramic crucible and heated with sulfuric acid, nitric acid / hydrochloric acid and hydrofluoric acid (selected according to the type of metal to be tested) in turn (carbonization on a hot plate + ashing in a muffle furnace) to digest it, then the volume is fixed and tested.
[0041] Examples 1 to 5 and Comparative Examples 1 to 5 are basically the same as Example 1, except for the heating method, container type, digestion solution composition and dosage, etc. The experimental design and results of Examples 1 to 5 and Comparative Examples 1 to 5 are shown in Table 1. The results of the digested solution after dry ashing method for Ca detection in Example 1 are shown in Table 1. Figure 2 .
[0042]
[0043] Experimental data show that the combination of the hot plate method and the detection method of mixed sulfuric acid, nitric acid and hydrofluoric acid as the digestion solution not only completely digests the sample (such as Figure 3 and Figure 4 As shown), it is pollution-free, and the test results have good accuracy and precision, making it suitable for promotion.
[0044] During the research and development process, the applicant found that factors such as heating method, container type, digestion solution composition and dosage all significantly affect the accuracy of the test results. Specifically, when microwave digestion is used to digest PET plastic samples, it cannot be completely digested, resulting in white powder or crystals at the bottom of the solution (such as Figure 1 The test results are inaccurate, with poor precision and repeatability. Specifically, except for the Ti test value in comparative example 6 using titanium dioxide as raw material and the Ca test values in embodiment 1 and comparative example 1, which are slightly higher than the test values in the embodiments and comparative examples of this scheme, the Ti test values obtained by microwave digestion are significantly lower than the Ti test values of this scheme. When the ceramic crucible and dry ashing method are used to digest the PET plastic sample (such as comparative example 1), although the sample can be basically digested (such as Figure 2 As shown), the test results are basically the same as those of the embodiment of this scheme, but because the crucible and hydrofluoric acid react to generate silicon tetrafluoride (SiF4) or other by-products, serious pollution is caused and potential safety hazards are increased, so it is not recommended to promote it. When a polytetrafluoroethylene beaker and dry ashing method are used in combination (such as Comparative Example 2), it has a lower Ti detection value than when the hot plate method is used to heat and digest the sample in Example 2, indicating that the dry ashing method cannot achieve the heating and digestion effect of the hot plate method when heated for the same time, thereby reducing the accuracy of its test results.
[0045] When hydrochloric acid is used instead of nitric acid (such as comparative example 3), there may be more undigested titanium compounds in the process of hydrochloric acid digestion of carbides, resulting in the inability to completely digest the titanium compounds even if the same amount of sulfuric acid carbonization and hydrofluoric acid are used to digest the titanium compounds, resulting in a significant decrease in the Ti detection value.
[0046] When the amount of sulfuric acid used during carbonization is too small (such as in Comparative Example 4), even if the other settings are the same as in Example 2, the titanium compound digestion effect will be reduced because the structure in the PET plastic cannot be completely carbonized, resulting in a Ti detection value that is significantly lower than the Ti detection value in Example 2 of this solution. If the amount of nitric acid used during digestion is too small (such as in Comparative Example 5), even if the other settings are the same as in Example 5, the impurities and metal elements in the carbide cannot be completely dissolved to fully release the titanium compound, resulting in a Ti detection value that is significantly lower than the Ti detection value in Example 5 of this solution.
[0047] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for testing the titanium and calcium content in titanium-containing PET plastics, characterized in that: When detecting titanium: it includes: (i) digestion stage: the sample is sequentially carbonized with sulfuric acid, nitric acid and hydrofluoric acid to digest the raw material, and the digestion solution is obtained by constant volume; (ii) detection stage: ICP-OES detects the digestion solution to obtain the titanium content; When calcium is detected: it includes (i) digestion stage: the sample is carbonized with sulfuric acid, digested with nitric acid or hydrochloric acid in turn, and the digestion solution is obtained by constant volume; (ii) Detection stage: ICP-OES detects the digestion solution to obtain the calcium content.
2. The method for testing the titanium and calcium contents in titanium-containing PET plastic according to claim 1, characterized in that: In the (i) digestion stage, the volume usage of the sulfuric acid, nitric acid and hydrofluoric acid is 10 to 25 times, 15 to 25 times and 10 to 20 times the mass of the sample, respectively.
3. The method for testing the titanium and calcium contents in titanium-containing PET plastic according to claim 1, characterized in that: In the digestion stage (i), polytetrafluoroethylene beakers are used as containers for the sulfuric acid carbonization raw material, nitric acid and hydrofluoric acid digestion, and heating is performed by a hot plate method.
4. The method for testing the titanium and calcium contents in titanium-containing PET plastic according to claim 2, characterized in that: In the (i) digestion stage, the endpoint of the sulfuric acid carbonization is to completely carbonize the sample into a black liquid, but not boil it dry.
5. The method for testing the titanium and calcium contents in titanium-containing PET plastic according to claim 2, characterized in that: In the (i) digestion stage, the endpoint of the nitric acid digestion is that the solution is clarified.
6. The method for testing the titanium and calcium contents in titanium-containing PET plastic according to claim 4 or 5, characterized in that: In the (i) digestion stage, after the hydrofluoric acid digestion, the digestion solution is filtered using a syringe filter.
7. The method for testing the titanium and calcium contents in titanium-containing PET plastic according to claim 1, characterized in that: In the (i) digestion stage, the volume of the digestion solution after constant volume is 100 to 150 times the mass of the sample.
8. The method for testing the titanium and calcium contents in titanium-containing PET plastic according to claim 1, characterized in that: In the (ii) detection stage, the digestion solution is diluted 50 to 100 times before detection.
Citation Information
Patent Citations
Digestion method and detection method of titanium-rich material
CN101315316A
Calcium base desulfurater primary and secondary content and impurity element simultaneous determination method
CN101598673A
Detection method for simultaneously detecting sixteen trace impurity elements in chromium carbide
CN113390860A
Novel wet digestion method
CN114739781A
Method for measuring content of titanium dioxide in livestock and poultry manure
CN115980020A